1983
DOI: 10.1159/000198945
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pentagastrin on the Motor Activity of the Dilated and Nondilated Sigmoid and Rectum in Chagas’ Disease

Abstract: In order to evaluate the effect of pentagastrin on the motor activity of the sigmoid and rectum in patients with Chagas’ disease, manometric studies were performed on 22 chagasic patients, 11 without and 11 with megacolon, and 11 control subjects. Pentagastrin had a stimulating effect on the sigmoid and rectum in control subjects as well as in chagasic patients without megacolon. In chagasic patients with megacolon, pentagastrin had no effect on sigmoid or rectum motility, probably as a result of the intrinsic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…Previous studies in Chagas disease patients have evidenced colonic hypomotility defined by low basal motility index and low wave frequency in the rectosigmoid, and impairment of the anorectal inhibitory reflex. 16,17 The results of these previous studies agree only partially with our findings: we observed that 28 of 69 (40.6%) patients with Chagas disease showed manometric evidence of anorectal motor dysfunction, but an abnormal anorectal inhibitory reflex was only confirmed in one asymptomatic patient.…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies in Chagas disease patients have evidenced colonic hypomotility defined by low basal motility index and low wave frequency in the rectosigmoid, and impairment of the anorectal inhibitory reflex. 16,17 The results of these previous studies agree only partially with our findings: we observed that 28 of 69 (40.6%) patients with Chagas disease showed manometric evidence of anorectal motor dysfunction, but an abnormal anorectal inhibitory reflex was only confirmed in one asymptomatic patient.…”
Section: Discussionsupporting
confidence: 73%
“…Degenerative changes in the intestinal wall together with a decrease in the number of nervous elements, and particularly neurons, in the region of the myenteric plexus have been confirmed. Such changes take place in the course of Chaga's disease, in which Trypanosoma cruzi parasites destroy the ENS, causing chronic constipation and leading to serious pathological widening of the large intestine [18,[20][21][22]. Taking into account the lack of nervous elements in the solid cancerous tumour destroying the wall of the intestine, as confirmed in this investigation, together with the results of investigations of other pathologies of the intestine, where destruction of the ENS leads to gradual constipation and widening of the colon, similar pathologic changes may be indicated as taking place also in the course of carcinoma of the large intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with megacolon (Fig. 7A) present long-term waves and hy- percontraction of muscle fibers, and these alterations are not detected in control individuals; the sigmoid colons of chagasic patients show low mobility with higher wave frequency rates than those of nonchagasic individuals (278). These abnormalities are attributed to neuron loss (Fig.…”
Section: Clinical and Pathological Presentations Of Chagas' Diseasementioning
confidence: 96%